Modular Organization of Engulfment Receptors and Proximal Signaling Networks: Avenues to Reprogram Phagocytosis - Britt, Emily A.; Gitau, Vanessa; Saha, Amara; Williamson, Adam P. (Frontiers in Immunology, 2021)
Transmembrane protein engulfment receptors expressed on the surface of phagocytes engage ligands on apoptotic cells and debris to initiate a sequence of events culminating in material internalization and immunologically beneficial outcomes. Engulfment receptors are modular, comprised of functionally independent extracellular ligation domains and cytosolic signaling motifs. Cognate kinases, adaptors, and phosphatases regulate engulfment by controlling the degree of receptor activation in phagocyte plasma membranes, thus acting as receptor-proximal signaling modules. Here, we review recent efforts to reprogram phagocytes using modular synthetic receptors composed of antibody-based extracellular domains fused to engulfment receptor signaling domains. To aid the development of new phagocyte reprogramming methods, we then define the kinases, adaptors, and phosphatases that regulate a conserved family of engulfment receptors. Finally, we discuss current challenges and opportunities for the field.